2019
DOI: 10.1111/jpm.12513
|View full text |Cite
|
Sign up to set email alerts
|

The impact of disability type and visibility on self‐concept and body image: Implications for mental health nursing

Abstract: Accessible summaryWhat is known on the subject?• Physical appearance, as in the case of individuals with physical disabilities who use a cane, walker or wheelchair, also influence others' reactions and as a result, may lead to one's negative or positive feelings and thoughts.• A disability that is not observable by others, as in the case of individuals with psychiatric disabilities (mental illnesses), may also have a negative impact on one's feelings and thoughts, due to stigma associated with psychiatric disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 62 publications
(74 reference statements)
0
25
0
6
Order By: Relevance
“…Shpigelman et.al, 2019 reported that individuals with invisible psychiatric disabilities have lower levels of self-concept and body image compared to individuals with visible physical disabilities. Gender, family status and the severity level of the disability were found to be associated with self-concept and body image [13]. Plana-Ripoll et.al, 2019 reported that, among respondents with at least 1 mental disorder, more or less 50% have 1 or more additional lifetime diagnoses [14].…”
Section: Fig-1: Changing the Conversation About Mental Health (Mh) [1]mentioning
confidence: 99%
“…Shpigelman et.al, 2019 reported that individuals with invisible psychiatric disabilities have lower levels of self-concept and body image compared to individuals with visible physical disabilities. Gender, family status and the severity level of the disability were found to be associated with self-concept and body image [13]. Plana-Ripoll et.al, 2019 reported that, among respondents with at least 1 mental disorder, more or less 50% have 1 or more additional lifetime diagnoses [14].…”
Section: Fig-1: Changing the Conversation About Mental Health (Mh) [1]mentioning
confidence: 99%
“…Finally, participants reported an improvement in their body image, as assessed by the BCS. People with physical disabilities are likely to experience a negative body image (because of the physical features of their disability) and to have difficulty in establishing a positive body image (Shpigelman and HaGani, 2019). However, Taleporos and McCabe (2002) demonstrated that some aspects of positive feedback from significant others and personal achievements, such as those in sports, a career or education, can contribute to the development of a positive body image in people with physical disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Shpigelman et.al, 2019 reported that individuals with silent psychiatric disabilities have lower levels of self-esteemand body image compared to individuals with visible physical disabilities. Gender, family status and the acerbity level of the infirmity were found to be correlated with self-esteem and body image [214]. Mental disorders and suicide resulting from work-load or work-related stress have become major occupational health issues worldwide, particularly in Asian countries [215].…”
Section: Psychiatric Disordersmentioning
confidence: 99%